Identification of 10 transcripts of FREP in penaeid shrimp Litopenaeus vannamei. (November 2016) - Hou, Fujun; Gao, Tiantian; Liu, Tao; Jia, Zhiying; Liu, Yongjie; Sun, Chengbo; Liu, Xiaolin
Abstract: Fibrinogen-related proteins (FREPs) are widely distributed in vertebrates and invertebrates and known having Fibrinogen-related domains (FReDs) which function in multiple aspects, especially in innate immune response as pattern recognition receptors. However, there is no any report about FREP in penaeid shrimp Litopenaeus vannamei . Here, totally 10 transcripts of FREP were isolated and named Lv FREP1.1, 1.2 until 1.10. All of the 10 transcripts have high identity in their 3′ ends and encode conserved FReDs. Since the 10 transcripts are highly similar we could not design any primers that can amplify a single transcript. We chose a pair of primers corresponding to part of Lv FREP1.1 and Lv FREP1.5 to examine their expression. Tissue distribution indicated Lv FREP1.1 and Lv FREP1.5 mRNA locates in hemocytes, gills, intestine, hearts and slightly in nerve. The expression of Lv FREP1.1 and Lv FREP1.5 behaves differently post bacteria and virus infection. Besides, recombinant Lv FReD could agglutinate bacteria Vibrio harveyi in the presence of Ca 2+ . These initial data presents the diversity of FREPs in penaeid shrimp and also push us to further explore their roles in shrimp immune response. Highlights: Totally 10 transcripts were identified and characterized in penaeid shrimp Litopenaeus vannamei. The tissue distribution and expression post bacteria and virus challenge were analyzed. Recombinant Lv FREP could agglutinate bacteria Vibrio harveyi in the presence of Ca 2+ .